Injectable collagen scaffold with human umbilical cord-derived mesenchymal stem cells promotes functional recovery in patients with spontaneous intracerebral hemorrhage: phase I clinical trial - Xiao-Yin Li; Wu-Sheng Deng; Zi-Qi Wang; Zheng-Chao Li; Shu-Lian Chen; Zhen Song; Quan Zhang; Jin Liang; Xu-Yi Chen (Neural Regeneration Research, 2023)
Animal experiments have shown that injectable collagen scaffold with human umbilical cord-derived mesenchymal stem cells can promote recovery from spinal cord injury. To investigate whether injectable collagen scaffold with human umbilical cord-derived mesenchymal stem cells can be used to treat spontaneous intracerebral hemorrhage, this non-randomized phase I clinical trial recruited patients who met the inclusion criteria and did not meet the exclusion criteria of spontaneous intracerebral hemorrhage treated in the Characteristic Medical Center of Chinese People’s Armed Police Force from May 2016 to December 2020. Patients were divided into three groups according to the clinical situation and patient benefit: control (n = 18), human umbilical cord-derived mesenchymal stem cells (n = 4), and combination (n = 8). The control group did not receive any transplantation. The human umbilical cord-derived mesenchymal stem cells group received human umbilical cord-derived mesenchymal stem cell transplantation. The combination group received injectable collagen scaffold with human umbilical cord-derived mesenchymal stem cells. Patients who received injectable collagen scaffold with human umbilical cord-derived mesenchymal stem cells had more remarkable improvements in activities of daily living and cognitive function and smaller foci of intracerebral hemorrhage-related encephalomalacia. Severe adverse events associated with cell transplantation were not observed. Injectable collagen scaffold with human umbilical cord-derived mesenchymal stem cells appears to have great potential treating spontaneous intracerebral hemorrhage.